Plug-and-play monitoring and performance optimization for industrial automation processes - Luo, Hao (Springer Vieweg, 2017)
Dr.-Ing. Hao Luo demonstrates the developments of advanced plug-and-play (PnP) process monitoring and control systems for industrial automation processes. With aid of the so-called Youla parameterization, a novel PnP process monitoring and control architecture (PnP-PMCA) with modularized components is proposed. To validate the developments, a case study on an industrial rolling mill benchmark is performed, and the real-time implementation on a laboratory brushless DC motor is presented.
Keywords: Plug and play (Computer architecture); elektronické knihy; electronic books